KURVA PERTAMBAHAN BOBOT BADAN DOMBA GARUT JANTAN 13-16 BULAN DIBERI 80% HIJAUAN DAN 20 % KONSENTRAT - Iman Hernaman; Raihan Nauval; Dedi Rahmat; Budi Ayuningsih; Tidi Dhalika; Fransiskus Teguh Santoso (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The research was carried out at the UPTD of the Margawati Sheep and Goat Breeding Center, the Department of Food Security and Livestock of West Java Province with the aim of finding a body weight gain curve model for Garut sheep. Eight male Garut sheep aged 13-16 months were reared for 12 weeks and given a ration with a composition of 80% forage and 20% concentrate. The sheep were measured and weighed every week during the study to obtain data on body weight gain. The collected data were analyzed using Curve Expert. The results showed that body weight gain increased until week 10 and then decreased until week 12 forming a curve. The Polynomial model curve gives the best curve with the equation = 2.61+9.53X-3.50X2+0.676X3-0.03X4 and has a standard error value (SE) of 7.27 and a coefficient of determination (R2) of 0.94.